The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/pathogens10040405
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Ocular Surface Microbial Profiles Revealed Discrepancies between Conjunctival and Corneal Microbiota

Abstract: The ocular microbiome composition has only been partially characterized. Here, we used RNA-sequencing (RNA-Seq) data to assess microbial diversity in human corneal tissue. Additionally, conjunctival swab samples were examined to characterize ocular surface microbiota. Short RNA-Seq reads, obtained from a previous transcriptome study of 50 corneal tissues, were mapped to the human reference genome GRCh38 to remove sequences of human origin. The unmapped reads were then used for taxonomic classification by compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…( Huang et al., 2016 ; Wang et al., 2019 ; Ren et al., 2020 ) In addition, conjunctival and corneal microbiome have very similar microbial taxonomic profiles with different proportion. ( Matysiak et al., 2021 ) Besides, previous studies have confirmed that different types of pathogens can invoke various ocular pathophysiological responses. ( Suzuki et al., 2010 ; Lobo et al., 2019 ) Our present work is thus aimed to extend the clinical application of high-throughput 16S rRNA gene sequencing, especially for the tissue diagnosis associated with a microbiota.…”
Section: Discussionmentioning
confidence: 93%
“…( Huang et al., 2016 ; Wang et al., 2019 ; Ren et al., 2020 ) In addition, conjunctival and corneal microbiome have very similar microbial taxonomic profiles with different proportion. ( Matysiak et al., 2021 ) Besides, previous studies have confirmed that different types of pathogens can invoke various ocular pathophysiological responses. ( Suzuki et al., 2010 ; Lobo et al., 2019 ) Our present work is thus aimed to extend the clinical application of high-throughput 16S rRNA gene sequencing, especially for the tissue diagnosis associated with a microbiota.…”
Section: Discussionmentioning
confidence: 93%
“…In this sense, applications of heatmaps to represent the presence or absence of microbial taxa and genes have been extensively reported in the literature. Some recent examples include the usage of heatmaps to elucidate the presence of coincident genes across microbial genomes [ 34 ] and coincident genera in human microbiota samples [ 35 ]. In the present study, most species belonging to the same genus were clustered together, highlighting common metabolic patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Alteration of the microbiota due to antibiotics usage was characterized with the reduction of some susceptible bacteria and the induction of microbial substitution. In addition, it was confirmed that antibiotic administered prophylactically before ophthalmic procedures may further reduce the ocular surface's amount and variety of microbiota [21,22]. Reasonably, we can accept that bacterial composition of the microbiota in bilateral cases was different from unilateral cases.…”
Section: Microbial Diversitymentioning
confidence: 90%